Описание личинки этиессы ингуматы - Aethiessa inhumata Gory et Perch. (Coleoptera, Scarabaeidae) - Медведев, С.И. (Вестник зоологии, 1968)
Aethiessa inhumata larva outwardly looks like larva of Cetonia and, especially, Po-tosia, but it differs from them in the dimensions of the first spiracle, and also in some details of spinule arrangement in symmetrical raws on the anal sternite. Imago and larvae of Aethiessa inhumata were found in a great quantity in a hole of Rhombomys opimus Licht. in north-west part of sandy desert Kizil-Kum in Kazakhstan and Uzbekistan. This fact adds to our knowledge of Aethiessa inhumata areal, because previously it was known only in Turkmenia, Afghanistan, Iran, Central Asia, Egypt.